IN SILICO MOLECULAR SCREENING AND DOCKING APPROACHES ON ANTINEOPLASTIC AGENT-IRINOTECAN TOWARDS THE MARKER PROTEINS OF COLON CANCER - V., MAHALEKSHMI; N., BALAKRISHNAN; T. V., AJAY KUMAR; V., PARTHASARATHY (International Journal of Applied Pharmaceutics, 2023)
Objective: The present investigation explores the binding affinities of Irinotecan, which is a topoisomerase I inhibitor, against the targets such as AKT1, TNKS-2, MMP, EGFR, TNKS-1, and BRAF, which are the protein that was overexpressed by colorectal carcinogenesis. Methods: In this study, the drug structure was drawn by chemdraw software and explored for its anti-cancer potential by Schrodinger software against selected targeted proteins such as epidermal growth factor receptor (EGFR), matrix metalloproteinase (MMPs), serine/threonine protein kinase Ba (AKT1), BRAF, tankyrases 1 (TNKS-1, and tankyrases 2 (TNKS-2). Results: From the results of docking analysis, the targets with the maximum binding affinity towards the preselected drug Irinotecan were further subjected to ADME prediction by the QikProp module of Schrodinger Maestro version 2018.4. Molecular docking analysis revealed that surface protein targets AKT1, TNKS-2, MMP, and EGFR have the highest binding affinity towards the selected topoisomerase I inhibitor Irinotecan when compared to TNKS-1 and BRAF targets. The higher docking score of Irinotecan with extracellular colorectal cancer target proteins was discovered in this investigation. Conclusion: Cancer is one of the most prevalent, lethal and risky malignant pathologies with an elevated prevalence and mortality rate worldwide. The current work will be more beneficial for rationalising the effective anticancer treatment according to the intensities of expression of the colon cancer target protein and for creating an optimum targeted drug delivery system of an anticancer agent to treat colon cancer.